Impact of Nutritional Interventions and Antenatal Care on Stunting in Indonesia: A Systematic Review - Limijadi, Edward Kurnia Setiawan; Devi, Katrin Setio (RSF Conference Series: Business, Management and Social Sciences, 2024)
Maternal nutrition is vital for fetal growth, infant health and survival, and long-term development. Indonesia is ranked as the country with the highest number of stunting cases in Southeast Asia. To address this, the government has prioritized preventing stunting by providing iron tables to adolescent girls, offering antenatal care (ANC) and nutritional interventions to pregnant women, and providing nutritional support to children. Despite some progress, the reduction rate still needs to be increased to meet targets, partly due to health services and resource disparities. This study systematically reviews the literature on the impact of nutritional interventions ANC on stunting prevention in Indonesia. This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles were sourced from Google Scholar, PubMed, Science Direct, Embase, and ProQuest databases, with only articles discussing the impact of nutrition and ANC interventions on stunting in Indonesia included. Two reviewers independently extracted the data and assessed the quality of the studies. Searches across five databases yielded 245 articles. After screening, ten articles were selected for analysis. The results indicated that nutrition and ANC interventions positively impacted the reduction of stunting prevalence, with several studies reporting significant reductions in areas such as Malang, Central Sulawesi, and Kalimantan. Further research is needed to assess the long-term effectiveness of these interventions and develop more effective and sustainable intervention models.